134k views
3 votes
W/c one of the ff is the invers of f(x)=2+e^x+1​

A, f(x)^-1=1+e^x B, f(x)^-1=1-ln(x-2)
C, f(x)^-1=1-e^x D,f(x)^-1=1+ln(x-2)

1 Answer

3 votes

Inverse function is y = -1 + ln(x-2)

Explanation:

To find the inverse of a function
y=f(x), we swap
x \textrm{ and }y and solve the equation to get the form
y=f(x). This is the inverse function.

On swapping
x \textrm{ and }y in
y=2+e^((x+1)), we get
x=2+e^((y+1)).


x-2=e^((y+1))


ln(x-2)=ln(e^((y+1)) )=y+1


y=-1+ln(x-2) is the inverse function.


f^(-1)(x)=-1+ln(x-2)

User Brabster
by
5.9k points